2002
DOI: 10.1038/sj.bjc.6600365
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterisation of a recombinant scFv reactive with human gastrointestinal carcinomas

Abstract: SC142-reactive antigen are highly glycosylated glycoproteins expressed on tissues of gastric and colon cancers but not on normal tissues. Murine SC142 antibody specific for the SC142-reactive antigen has been produced by immunisation with SNU16 stomach cancer cells. However, SC142 antibody has several potential problems such as high immunogenicity and poor tumour penetration owing to their large size. To improve tumour penetration potential in vivo, recombinant single-chain fragments have been produced using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 20 publications
(17 reference statements)
1
8
0
Order By: Relevance
“…We feel that this result corresponds with the anti-CD3 scFv-B7.1 fusion protein expressed on the surface of HeLa cells binding to T lymphocytes and strongly inducing T-cell activation (Yang et al, 2007b). Furthermore, many reports have described the same binding specificity and affinity of scFv as the monomeric form of their parental antibody (Bedzyk et al, 1990;Pantoliano et al, 1991;Kim et al, 2002). Our results indicate that in the absence of cross-linking and covalent dimerization of parental CD147 mAb, the monomeric form of anti-CD147 molecules can mediate signal transduction and exhibit biological activity in T cells through their antigenspecific domain.…”
Section: Discussionsupporting
confidence: 73%
“…We feel that this result corresponds with the anti-CD3 scFv-B7.1 fusion protein expressed on the surface of HeLa cells binding to T lymphocytes and strongly inducing T-cell activation (Yang et al, 2007b). Furthermore, many reports have described the same binding specificity and affinity of scFv as the monomeric form of their parental antibody (Bedzyk et al, 1990;Pantoliano et al, 1991;Kim et al, 2002). Our results indicate that in the absence of cross-linking and covalent dimerization of parental CD147 mAb, the monomeric form of anti-CD147 molecules can mediate signal transduction and exhibit biological activity in T cells through their antigenspecific domain.…”
Section: Discussionsupporting
confidence: 73%
“…43 Because of their small size (1/6th the size of intact IgG), low kidney uptake, and rapid blood clearance, scFvs are being increasingly used in cancer research as carrier of radionuclei and drugs to tumors. 44 Therefore, an scFv that specifically hydrolyzes Ab represents a promising therapeutic option for treating AD. We previously identified a light chain antibody mk18, and the scFv derivative c23.5, both of which have a-secretase-like activity.…”
Section: Resultsmentioning
confidence: 99%
“…The scFv is the smallest functional modules of antibody molecule; the lack of Fc domains makes it less immunogenic responsive [36,37], which may result in efficient protection against infection with different serotypes of E. tarda. Additionally, studies demonstrated that when the linker length was ,25 amino acids, scFvs in the V Llinker-V H format had stronger binding activity than those with the V H -linker-V L format [43][44][45].…”
Section: Evaluation Of Vaccine Efficacymentioning
confidence: 99%
“…In addition, the lack of Fc domain makes scFv less immunogenic responsive. These characteristics make scFv potentially useful in diagnosis and therapy [36,37]. The common flexible linker (Gly 4 Ser) 3 , which connects V H and V L , may substitute for constant region contacts in the Fab and thereby help recover the native binding properties in the scFv [38].…”
Section: Introductionmentioning
confidence: 99%